Implementasi Pendidikan Karakter dan Nilai Religius Siswa Melalui Seni Budaya Debus Banten - Suryadi Suryadi (Peneliti.net, 2022)
The cultural art of Debus Banten is the cultural heritage of the ancestors who came from Banten. The purpose of this study was to determine the character and value education of students through the arts and culture of Debus Banten. This study uses ethnographic qualitative research methods. Sources of research data are: (1) written sources, (2) oral sources, (3) documents and (5) recordings. Data collection techniques are observation, interviews, and documentation. Data analysis was carried out since, before, during, and before the study using qualitative descriptive techniques. The research found that character education and religious values ​​of students through the arts and culture of Debus Banten include: character education, hard work, perseverance, patience, independence, discipline, and religious values. . character education in students is carried out at home, in the community and at school; Through the cultural arts of Banten Debus, the character education of students and the religious values ​​of students can be embedded in the personality of the students, the Debus Culture of Banten is one of the media for character education of students.